Glut3 overexpression improves environmental glucose uptake and antitumor efficacy of CAR-T cells in solid tumors - Hui Wang; Yi Zhang; Feng Li; Shasha Liu; Shumin Wang; Wenhao Hu; Yue Liang; Chunyi Shen; Yuyu Zhao (Journal for ImmunoTherapy of Cancer)
Background Glucose deprivation inhibits T-cell metabolism and function. Glucose levels are low in the tumor microenvironment of solid tumors and insufficient glucose uptake limits the antitumor response of T cells. Furthermore, glucose restriction can contribute to the failure of chimeric antigen receptor T (CAR-T) cell therapy for solid tumors. However, the impact of glucose restriction remains unknown in CAR-T cell therapy.Methods Glucose transporters were detected and overexpressed in CAR-T cells. The impacts of glucose restriction on CAR-T cells were checked in vitro and in vivo.Results Glucose restriction significantly decreased CAR-T cell activation, effector function, and expansion. CAR-T cells expressed high levels of the glucose transporter Glut1, which has a low affinity for glucose. Overexpression of Glut1 failed to improve CAR-T cell function under glucose-restricted conditions. In contrast, the function and antitumor potential of CAR-T cells was enhanced by the overexpression of Glut3, which has the highest affinity for glucose among the Glut transporter family and is expressed in minor parts of CAR-T cells. Glut3-overexpressing CAR-T cells demonstrated increased tumoricidal efficacy in multiple xenografts and syngenetic mouse models. Furthermore, Glut3 overexpression activated the PI3K/Akt pathway and increased OXPHOS and mitochondrial fitness.Conclusions We provide a direct and effective approach to enhance low glucose uptake levels by CAR-T cells and improve their antitumor efficacy against solid tumors.